Pocket Vienna : top experiences, local life - Le Nevez, Catherine ({Not Specific}: Lonely Planet, 2022)
"Lonely Planet's Pocket Vienna is your guide to the city's best experiences and local life -by neighbourhood. Sample the brew at a Kaffeehauser, wander the baroque streets, visit an imperial palace; all with your trusted travel companion. Uncover the best of Vienna and make the most of your trip!" Publisher's description.
Keywords: Austria Vienna; Vienna (Austria) Guidebooks